Taklim Sharaf bi Istimal Kitab Al-salsal Al-madkhal fi Madrasah Tarbiyah Islamiah Candung - Rahmi Dwi Mulia (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2022)
The researcher chose this topic because the researcher found differences in the form of presentation of the sharaf material from the previous book, and the material covered in it was more complete and systematic.How to learn sharaf using the book of Salsal Madkhal at Madrasah Tarbiyah Islamiah Candung? The purpose of this research is to reveal the teaching sharaf using the book of Salsal Madkhal in terms of the objectives, materials, methods and means of teaching sharaf and its evaluation. This research is based on field research using a descriptive methodology. The tools to collect i formation are observation, interviews, and documentation. After researched about teaching sharaf in this institution, she concluded that the purpose of teaching sharaf using the book of Salsal Madkhal in this institution is for students are able to change the form of an arabic sentence to another form and know the origin of the sentence, and students to be able to read and translate Arabic texts. And able to parse correct Arabic sentences. Sharaf learning materials in the Salsal Madkhal book are thirty-five chapters of fi’il, tashrif and their i’lal. The method of teaching sharaf at the Madrasah Tarbiyah Islamiah Candung is the standard method. And the facilities used are visual aids such as whiteboards, markers and books. And evaluation of learning sharaf at Madrasah Tarbiyah Islamiah Candung in the form of written tests and oral tests, which are carried out twice in one semester.